Early Second-Look Hysteroscopy: Prevention and Treatment of Intrauterine Post-surgical Adhesions - Sebbag, Lauren; Even, Marc; Fay, Stéphanie; Naoura, Iptissem; Revaux, Aurélie; Carbonnel, Marie; Pirtea, Paul; de Ziegler, Dominique; Ayoubi, Jean-Marc (Frontiers in Surgery, 2019)
Introduction IUA (Intra-uterine adhesion) is one of the main causes of secondary infertility. The aim of this study was to evaluate the prevalence of IUA developing in women undergoing hysteroscopic resection for submucous myomas, polyps and intrauterine synechiae and test the efficacy of second look hysteroscopy for diagnosing and treating post-surgical adhesions. Materials and Methods We retrospectively collected data from reproductive age women who had a second look office hysteroscopy following hysteroscopic resection for myoma, polyp or IUA at Foch hospital (Suresnes, France) between 2009 and 2017. Results 622 reproductive-age women underwent hysteroscopic resection for myoma, polyp and/or IUA. Among them, 155 women had a second look hysteroscopy. In this group, 29/155 (18.7%) had IUA formation: 17/83 (20.5%) women who underwent hysteroscopic myomectomy, 5/46 (10.9%) women who underwent hysteroscopic polypectomy and 7/26 (26.9%) women who underwent hysteroscopic lysis of adhesions. These IUA have been lysed by the office hysteroscopy procedure in 16/29 (55.2%) patients: 11/17 (64.7%), 2/5 (40%) and 3/7 (42.9%) in women who underwent hysteroscopic myomectomy, polypectomy and lysis of adhesion, respectively. Conclusions; IUA is a common complication of hysteroscopic surgery. Second look office hysteroscopy is an easy and effective procedure for diagnosing and removing newly formed IUA. It should be recommended for all women undergoing hysteroscopic resection for myomas, polyps or IUA.